Da soberania no contexto do comércio internacional: os regimes de soberania de Agnew e a atuação de atores não-estatais - Gabriel Pedro Moreira Damasceno (2019)
The emergence and strengthening of non-state actors in International Trade challenge the classical understandings of supposedly absolute sovereignty. This paper contextualizes the evolutionary link between the institute of sovereignty and International Trade, demonstrating that its understanding is inseparable. Through an interdisciplinary approach between theories of International Law, Geopolitics and International Relations, we sought to understand sovereignty as an extraterritorialinstitute, and that its exercise can be exercised in four different regimes: classical, globalist, imperialist/cooperative and integrative, as advocated by John Agnew. Afterwards, in the light of Agnew's theories, it is analyzed in which regime is the exercise of sovereignty by States in International Trade, analyzing the performance of non-state actors, specifically the World Trade Organization and Non-Governmental Organizations in this scenario. Finally, it is concluded that, with regard to the exercise of sovereignty in international trade, non-state actors would be responsible for adapting it to the cooperative regime.